Taiwanese students in Malaysia and interculturality: when national identities take primacy over individualities - Machart, Regis Christian; Lim, Sep Neo; Yeow, E-Lynn; Chin, Sin Zi (Brill Academic Publishers, 2014)
Using a liquid approach, the authors analyze the intercultural discourse of Taiwanese students who had taken part in a short term exchange program with a Malaysian university. The four participants were graduating in Mandarin Chinese in their home institution and were following a Chinese program in multilingual Malaysia. Data were collected through focus groups held in Mandarin Chinese and focused on their experience in the host country. The authors analyze how participants talk about themselves, Malaysians, and their adaptation to the host country. The processes of essentialization and othering that occur and put in contrast the host and the home contexts are similar to those held in Asia-to-Europe mobility and very far from an “interculturality without culture” (Dervin, 2010). If we focus on the construction of discourses, this Asia-to-Asia mobility forces us to relativize the opposition of cultures as an explanation for difficulties encountered by mobile students.